When the Focus of the Text is Blurred: A Textlinguistic Approach for Analyzing Student Interpreters' Errors - Shakir, Abdullah; Farghal, Mohammed (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThis study aims to investigate the effect of missing the pragmatic impact of two textual components, viz., conjunctives and key lexical items, on the typological focus of the source text in the process of simultaneous interpreting from Arabic into English. The source text assumes a hortative function which calls into the recipient's active socio-historical memory, events and experiences comparable to those addressed in the text. The investigation is based on the assumption that in a hortative text conjunctives and lexical items play a significant role in displaying the pragmatics of the communicative event. The study investigates how five Arabic conjunctives and four emotively-loaded lexical items in the text were rendered in English by ten MA. (Translation) students. This research has shown that the conjunctives were inappropriately rendered by most of the student interpreters, and that such renderings distorted the intended argument of the text. Results also reveals that the interpretations provided of the four key lexical items stripped them of their emotive charge, thus neutralizing the argument of the text. The study concludes with suggestions concerning the methods of teaching interpreting and the content of the interpreting course at Yarmouk University. The suggestions are based on the implications derived from the analysis of both the source text and the students' renderings of the conjunctives and the lexical items.